Integrated Marketing Communication Model in Building the Image of Tourist Attractions in Kota Tua Jakarta - Murhadi; Derinta Entas; Nenny Wahyuni (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: This research aims to harmonize marketing communication strategies and programs to create interesting messages and information. Research Methods: The research uses a qualitative approach, namely the assessment of how Integrated Marketing Communication strategies and models in integrating the marketing communication mix. Kota Tua Jakarta (the Old City Jakarta) became a locus in this study. Observation, interview, documentation, and focus group discussion are research data collection techniques. Results and discussion: The delivery of promotions and publications is directed at electronic media and social media by the reputation and target audience. Kuta Tua Jakarta’s website is designed to follow the dominant identity of building colors and tourist attractions from communities that are members of one community. Regional structuring and improving facilities and infrastructure and strengthening the cooperation network with stakeholders are the priorities of the manager. Implication: The concept of the Integrated Marketing Communication model with planning is presented through organizational communication among stakeholders. Keywords: IMC model, marketing communication mix, tourism product.